2013
DOI: 10.1021/jp305455v
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Hydrogen Bonding and Molecule–Substrate Interactions in the Case of Terephthalic Acid Molecules on Cu(001) Surfaces

Abstract: The adsorption and self-assembling properties of terephthalic acid (TPA) molecules deposited on Cu(001) at room temperature have been systematically studied with both experimental and theoretical tools. The system forms two phases at room temperature: the metastable β-phase and the stable (3 × 3) one. In the case of the β phase, low-energy electron diffraction and scanning tunneling microscopy (STM) results indicate that it has a (9√2 × 2√2) R45° unit cell with exactly the same molecular coverage as the (3 × 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 41 publications
7
48
0
Order By: Relevance
“…In particular, molecules with more than one H-bond donor and/or acceptor can explore a rich configurational space with multiple local minima, potentially forming structures significantly different than those created when only a single synthon is present. [20][21][22][23][24] Here, we describe the deposition of ferrocenedicarboxylic acid (Fc(COOH) 2 ) from solution onto clean Au(111) surfaces. We have previously found that ferrocene with a single COOH group (FcCOOH) forms a variety of complex structures due to the combination of strong COOH-derived hydrogen bonding with C-H• • • O hydrogen bonding; these structures include a cyclic pentamer that assembles aperiodically at high surface coverage to make a two-dimensional quasicrystal.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, molecules with more than one H-bond donor and/or acceptor can explore a rich configurational space with multiple local minima, potentially forming structures significantly different than those created when only a single synthon is present. [20][21][22][23][24] Here, we describe the deposition of ferrocenedicarboxylic acid (Fc(COOH) 2 ) from solution onto clean Au(111) surfaces. We have previously found that ferrocene with a single COOH group (FcCOOH) forms a variety of complex structures due to the combination of strong COOH-derived hydrogen bonding with C-H• • • O hydrogen bonding; these structures include a cyclic pentamer that assembles aperiodically at high surface coverage to make a two-dimensional quasicrystal.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during our experiments, the intermolecular distances around the defects remain identical to those measured in the pristine lattice. Previous investigations on these molecules demonstrate that these defects are related to the partial deprotonation of the TPA 2,16,18 . Indeed, these latter are not due to the presence of a vacancy in the assembly but to a subtle modification of the contrast between two TPA.…”
Section: Evolution Of the Self-assemblymentioning
confidence: 93%
“…These molecules are also able to form 2D metal-ligand coordination arrays for example with magnetic atoms such as the high-spin Fe(TPA) 4 assemblies obtained by Gambardella et al on Cu(100) surfaces and conducive to investigations concerning magnetic anisotropy 14 . On the same surface, different studies demonstrate the formation of three different lattices depending on the temperature of the metallic surface during molecule deposition, these networks being also linked to a partial or total deprotonation of TPA 2,15,16 . Recently, White et al use the same molecules on Cu(111) as a model system to study the well-known interplay between intermolecular and adsorbate-substrate interactions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing -COOH groups can provide two hydrogen bonds, which are particularly promising and reliable in creating and maintaining surface order. The self-assembly aggregates formed in benzoic acid solutions depends on the number and relative placement of carboxylic acid groups (Lackinge and Heckl 2009;Clair et al 2004;Fuhr et al 2013;Heininger et al 2009;Ye et al 2007). The self-assembly of the derivatives of dibenzothiophene with carboxyl groups affects the physicochemical properties of asphaltenes.…”
Section: Introductionmentioning
confidence: 99%